Islamic Education Management in Islamic Boarding Schools: Integration of Ecological Values ​​in the Educational Curriculum - Nurul Latifatul Inayati; Abil Fida Muhammad Qois Al Hadi; Fadhia Ananda; Istanto; Fadhilla Nangroe Anggraini; Rabi’atul’adawiyah Binti Jamaludin (Mapendis: Jurnal Manajemen Pendidikan Islam, 2025)
Climate change and environmental degradation are global challenges that demand the involvement of the education sector in sustainable development. In Indonesia, pesantren as traditional Islamic educational institutions have a strategic position because they not only transmit religious knowledge, but also shape the social values and practices of the community. Some Islamic boarding schools have developed waste management, renewable energy, and organic farming programs, but these initiatives are still sporadic and rarely systematically studied. This research aims to examine the contribution of pesantren to environmental education and sustainable development, identify practices, challenges, and opportunities that arise, as well as map the latest research trends. The study was conducted with a Systematic Literature Review (SLR) using the PRISMA 2020 framework. Literature searches on Scopus, Web of Science, and Google Scholar (2020–2025) using Boolean strings: TITLE-ABS-KEY ("pesantren" OR "Islamic boarding school") AND TITLE-ABS-KEY ("sustainability" OR "sustainable development" OR "environmental education" OR "environmental issues"). Of the 77 articles identified, 30 met the inclusion criteria and were analyzed descriptively and thematically. The findings show that pesantren integrate Education for Sustainable Development (ESD) with a spiritual dimension—khalīfah, amanah, ihsan—that places ecological practices as worship. The main themes include curriculum-based and extracurricular environmental education, green pesantren management, and contribution to the SDGs through renewable energy and waste management. Challenges include limited funding, cultural resistance, and weak policy support. Pesantren play a strategic role in sustainable development by connecting religious norms and ecological practices. Follow-up research with a mixed-methods approach, standardized indicators, and longitudinal studies is urgently needed, while policies in the form of eco-pesantren standards, performance-based incentives, and integration into the SDGs monitoring system will strengthen the contribution of pesantren at the national and global levels.